Reinterpretation of Tarekat and the Teachings of Sufism According to Said Nursi - Cemal Sahin; Zaimul Asroor (Millah: Journal of Religious Studies, 2021)
In this modern-contemporary era, Muslims are often faced with the question, â€œIs it necessary to follow the teachings of the tarekat? Didnâ€™t the tarekat (especially after al-Ghazali criticized the philosophical tradition) cause Muslims to decline and lose their critical power?â€ Moreover, some sufism teachings such as wahdatul wujud, wahdatus syuhud etc. Often considered as deviating from the pure teachings of Islam, especially by the Wahabi group. In order to answer some of these questions, the writer tries to present how Said Nursi responds in the interpretation of Risalah Nur. Nursi said that, "The present time is not the time of the tarekat." If it is not understood comprehensively, it will cause the reader to be inaccurate in concluding that generally Nursi rejects tarekat and some sufism teachings. That is why the writer wants to present which side of the teachings of tarekat and sufism that Nursi criticizes and what is his new offer. The research method that the author uses is library research with a socio-historical and descriptive-analysis approach using Risalah Nur as the primary source and several supporting books that are still related to the theme as a secondary source. The writer finds that sufism and tarekat are still important parts of Islamic teachings according to Nursi. But, he believes that what is more important now is to understand well the essense of religion rather than following the sufism path. He also concludes that the peak stage of sufism is maâ€™rifatullah.